Book Review: A Life-story of a Professorship: Nordisk etnologi 1921–2021: Ett ämne i rörelse [Nordic Ethnology 1921–2021: a University Subject in Motion]. Fredrik Nilsson & Anna-Maria Åström (Eds). 2021. 447 pp. ISBN 978-951-765-998-7 - Kallberg, Ulla (Association of Finnish ethnologists, Ethnos ry, 2025)
​​​​​​​